Impairment of myocardial perfusion correlates with heart failure severity in patients with non‐compaction cardiomyopathy - Andraz Cerar; Martina Jaklic; Sabina Frljak; Gregor Poglajen; Gregor Zemljic; Barbara Guzic Salobir; Maja Dolenc Novak; Monika Stalc; Rok Zbacnik; Mirta Kozelj (ESC Heart Failure, 2020)
ABSTRACT Aims Non‐compaction cardiomyopathy (NCM) is a congenital heart disease characterized by an arrest of the myocardial compaction process. Although NCM patients have impaired formation of microvasculature, the functional impact of these changes remains undefined. We sought to analyse a potential correlation between myocardial ischemia and heart failure severity in NCM patients. Methods and results We enrolled 41 NCM patients (28 male and 13 female), aged 21–70 years. In all patients, we have determined left ventricular end‐diastolic volume (LVEDV), left ventricular ejection fraction (LVEF), and global longitudinal strain (GLS) by echocardiography. At the same time, serum levels of N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) have been measured, and myocardial single‐photon emission computed tomography at rest and on stress was used to define significant myocardial ischemia defined as summed difference score ≥ 2. Myocardial ischemia has been demonstrated in 11 patients (27%, Group A), and 30 patients showed no significant ischemic changes (73%, Group B). The groups did not differ in sex, age, kidney, or liver function. When compared with Group B, Group A had significantly lower LVEF (35 ± 15% in Group A vs. 53 ± 11% in Group B, P < 0.001), higher LVEDV (188 ± 52 mL vs. 136 ± 52 mL, P = 0.007), lower GLS (−9.9 ± 5.2% vs. −14.5 ± 4.1%, P = 0.001), and higher NT‐proBNP levels (1691 ± 1883 pg/mL vs. 422 ± 877 pg/mL, P = 0.006). Overall, higher summed difference score was associated with lower LVEF (r = −0.48, P = 0.001), higher LVEDV (r = 0.39, P = 0.012), lower GLS (r = 0.352, P = 0.024), and higher levels of NT‐proBNP (r = 0.66, P < 0.001). Conclusions The presence of myocardial ischemia in patients with NCM is associated with worse left ventricular function, dilation of the left ventricle, and more pronounced neurohumoral activation.